Export of wooden furniture by Malaysia (2000-2003) / Rozita Ismail - Ismail, Rozita (2004)
This paper project is covered about the export of Malaysian wooden furniture beginning on the year 2000 to 2003. The some of the ASEAN country were selected randomly based on the country that being members with Malaysia in import and export trade involved furniture. The main reason for th.is paper project is to determine the factors that are influences in either increase or decrease the value of the export. This research is much refers on the Internet and also the wood magazine, Malaysia Timber Bulletin and MASKAYU and also the data that has been published by MATRADE, MTIB and MTC.